The Effect of Corporate Social Responsibility Disclosures to Tax Avoidance (In a Company Listed on the Indonesian Stock Exchange 2015-2016) - Linda Febriana, Suhendro & Yuli Chomsatu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aimed to obtain empirical evidence of the influence of CorporateSocial Responsibility (CSR) to tax avoidance. In this research are independentvariables used to disclosure of CSR economic dimension, CSR environmentaldimension and CSR social dimension. While the dependent variable, in thisresearch is the tax avoidance.The samples that used in this research is companieslisted on the Indonesia Stock Exchange (BEI), based on purpose sampling methodwas obtained 44 companies. Observation period was 2015-2016. Corporate taxavoidance is proxy by ETR. The indicators disclosure of CSR is using GlobalReporting Intiative (GRI) guideline. The data in this research was processed usingSPSS in multiple regression method. The result of this research shows that CSReconomic dimensionand CSR social dimension does not have significant influenceto tax avoidance. While CSR environmental dimension have significant influenceto tax avoidance.Keyword: CSR economic dimension; CSR environmental dimension; CSR social dimension;ETR and tax avoidance.